Method for in-situ growth of zinc-magnesium-aluminum ternary hydrotalcite coating on surface of aluminum alloy

By growing zinc, magnesium, aluminum ternary hydrotalcite coatings in situ on the surface of aluminum alloys, the problem of insufficient corrosion resistance in the marine environment of existing binary metal hydrotalcite coatings is solved, and higher corrosion resistance and reliability are achieved, and suitable for more demanding environments.

CN119592931APending Publication Date: 2025-03-11SHENYANG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411777820.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing binary metal hydrotalcite coatings cannot meet engineering needs in extremely demanding marine environments, and the main laminate composition has a great impact on corrosion resistance and load-release behavior of corrosion inhibitors, making it difficult to meet higher corrosion resistance requirements.

Method used

The zinc-magnesium-aluminum ternary hydrotalcite coating was directly grown on the surface of the aluminum alloy by in situ growth method. By preparing an in situ growth solution containing magnesium nitrate, zinc nitrate and urea, it was grown in situ under mild reaction conditions to form a ternary hydrotalcite coating that was well-bound to the aluminum alloy matrix.

Benefits of technology

It achieves higher corrosion resistance and reliability. Compared with binary hydrotalcite coatings, the corrosion resistance of zinc, magnesium, aluminum ternary hydrotalcite coatings is significantly improved, has a wider application, and is energy-saving in the preparation process and is easy to operate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119592931A_ABST
    Figure CN119592931A_ABST
Patent Text Reader

Abstract

The invention discloses a method for in-situ growth of a zinc-magnesium-aluminum ternary hydrotalcite coating on an aluminum alloy surface, and belongs to the technical field of aluminum alloy surface protection treatment, and the method comprises the following steps: (1) carrying out pretreatment on the aluminum alloy surface; (2) preparing an in-situ growth solution; (3) the treated aluminum alloy base material is placed in an in-situ growth solution for in-situ growth; (4) washing and drying to prepare a zinc-magnesium-aluminum hydrotalcite coating; according to the method, the zinc-magnesium-aluminum hydrotalcite coating directly grows on the aluminum alloy base material in situ in one step through the in-situ growth method, the preparation method breaks away from a high-temperature and high-pressure reaction kettle used in a traditional method, the preparation conditions are milder, the process is simple, operation is easy, and the applicability is wider. The ternary zinc-magnesium-aluminum hydrotalcite coating disclosed by the invention is uniform and compact, has strong binding force with an aluminum alloy substrate, and can obviously improve the corrosion resistance of the aluminum alloy substrate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of aluminum alloy surface protection treatment, and specifically relates to a method for in-situ growing a zinc-magnesium-aluminum ternary hydrotalcite coating on the surface of an aluminum alloy. Background Art

[0002] Aluminum alloy has the advantages of low density, high thermal conductivity, high electrical conductivity, low price, etc., so it is widely used in the fields of shipbuilding, aerospace, weapons and nuclear industry. Especially in recent years, under the guidance of the concept of lightweight equipment manufacturing, aluminum alloy will play an increasingly important role in the field of advanced equipment manufacturing. Aluminum alloy is very prone to pitting, stress corrosion and corrosion fatigue in corrosive environments such as humid air and marine atmosphere, which seriously reduces the safety, reliability and service life of aluminum alloy. Therefore, in order to expand the scope of use of aluminum alloy, it is necessary to perform surface treatment on aluminum alloy to improve the corrosion resistance of the matrix.

[0003] In recent years, hydrotalcite compounds have become a new type of environmentally friendly intelligent protective coating material that has attracted much attention due to their unique layered structure, high specific surface area and excellent anion exchange performance. Hydrotalcite compounds include hydrotalcite and hydrotalcite-like compounds. Their main body is generally composed of two metal hydroxides, so they are also called layered double metal hydroxides. There are many methods for synthesizing hydrotalcite, including co-precipitation, ion exchange, roasting and reduction, hydrothermal synthesis, in-situ growth, etc. Among them, the in-situ growth method is to directly grow the hydrotalcite coating on the metal surface by providing relevant ions from the matrix. The preparation process is simple, the bonding strength with the metal matrix is ​​strong, and the corrosion resistance is good. It shows broad application prospects in the field of corrosion protection of aluminum alloys.

[0004] In the existing technical solutions, the hydrotalcite-like coatings used on the surface of aluminum and aluminum alloys are mostly binary metal hydrotalcite-like coatings such as Zn-Al, Mg-Al, and Ni-Al, which can improve the corrosion resistance of aluminum alloys to a certain extent. For example, a Chinese patent (patent number CN 109853022 A) discloses a method for preparing a corrosion-resistant Mg-Al LDH / MAO composite coating for aluminum alloys. The corrosion current density of the prepared composite coating is about 10 -6 A.cm -2 The Chinese patent (patent number CN 103184447 B) discloses a self-repairing anti-corrosion conversion film on the surface of aluminum and its alloys and its preparation method. The corrosion current of the prepared magnesium-aluminum hydrotalcite conversion film is 1.14×10 -8 mA·cm -2 , the impedance is 4.7×10 5 Ω·cm -2Although the existing technology can improve the corrosion resistance of aluminum alloy substrates to a certain extent, binary metal hydrotalcite coatings still cannot meet engineering requirements in the face of extremely harsh marine environments. In addition, since the composition of the main layer can affect the corrosion resistance of the hydrotalcite coating and the load-release behavior of the corrosion inhibitor to a certain extent, it is necessary to explore the preparation method of multi-component hydrotalcite coatings. Summary of the invention

[0005] In order to solve the problems mentioned in the background technology, the purpose of the present invention is to provide a method for in-situ growing a zinc-magnesium-aluminum ternary hydrotalcite coating on the surface of an aluminum alloy. The present invention adopts an in-situ growth method to directly grow a new type of ternary system hydrotalcite coating on the surface of an aluminum alloy in situ. The coating is well combined with the aluminum alloy substrate, and the corrosion resistance and reliability of the aluminum alloy are effectively improved. The specific preparation method comprises the following steps: a. Pre-treating the aluminum alloy surface: grinding the aluminum alloy substrate to remove surface pollutants and oxides, rinsing, immersing in ethanol solution and deionized water for ultrasonic cleaning, and drying to obtain a pre-treated aluminum alloy substrate; b. Prepare in situ growth solution: dissolve 0.005-0.1M magnesium nitrate, 0.005-0.1M zinc nitrate and 0.1-0.5M urea in deionized water, adjust the pH to 8-11, and then stir in a magnetic stirrer to prepare an in situ growth solution; c. In-situ growth of hydrotalcite coating: the pre-treated aluminum alloy is placed in an in-situ growth solution for in-situ growth, the reaction temperature is 65 to 95°C, and the reaction time is 6 to 24 hours; d. Cleaning and drying: Rinse the aluminum alloy after the reaction with deionized water and then dry it in a drying oven at 60°C for 12 hours.

[0006] In the step a, the aluminum alloy grade is 5052.

[0007] In the step a, the size of the aluminum alloy substrate is (15-20) mm×(10-15) mm×(1-2) mm (length×width×height).

[0008] In the step a, the aluminum alloy substrate is polished using sandpaper with a mesh size of 800#-2000# in sequence; the sandpaper is water-resistant SiC sandpaper.

[0009] In the step a, the volume percentage concentration of the ethanol solution is 95%.

[0010] In the step a, the ultrasonic cleaning treatment time is 15-30 minutes.

[0011] In the step b, the pH is adjusted using a NaOH solution with a concentration of 1.0 mol / L.

[0012] In the step b, the in-situ growth liquid is stirred in a magnetic stirrer for 30 minutes.

[0013] In step c, the aluminum alloy substrate treated in step a is placed in the in-situ growth solution of step b, and can be suspended so that hydrotalcite can be grown in-situ on both sides of the substrate. If only one side needs to grow, it can be placed flat on the bottom.

[0014] In the step c, the in-situ growth is carried out in a water bath.

[0015] The beneficial effects of the present invention are: (1) The method provided by the present invention for in-situ growth of a zinc-magnesium-aluminum ternary hydrotalcite coating on an aluminum alloy surface eliminates the extreme reaction conditions of a traditional high-temperature and high-pressure reactor, and has mild reaction conditions, more energy-saving, more convenient operation, and more practical industrial production characteristics. The preparation process is not limited by the size and shape of the sample, and has a wider applicability; (2) The corrosion resistance of the zinc-magnesium-aluminum ternary hydrotalcite coating prepared by the present invention is better than that of the binary hydrotalcite coating prepared under the same conditions; (3) The present invention generates a zinc-magnesium-aluminum ternary hydrotalcite coating in situ on the substrate surface in one step. The coating is uniform and dense, and is well bonded to the substrate, thereby effectively improving the corrosion resistance of the aluminum alloy. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to make the purpose, technical solution and beneficial effects of the present invention clearer, the present invention provides the following drawings for illustration: Figure 1 The present invention is a scanning electron microscope photograph of a hydrotalcite coating prepared on the surface of an aluminum alloy substrate, wherein Figures (a) to (d) are scanning electron microscope photographs of the zinc-magnesium-aluminum ternary hydrotalcite coating prepared in Examples 1 to 4, respectively, and Figure (e) is a scanning electron microscope photograph of the magnesium-aluminum binary hydrotalcite coating prepared in Comparative Example 1; Figure 2 The EDS spectra of the hydrotalcite coating prepared on the surface of the aluminum alloy substrate according to the present invention, wherein Figure (a) is the EDS spectrum of the zinc-magnesium-aluminum ternary hydrotalcite coating prepared in Example 3, and Figure (b) is the EDS spectrum of the magnesium-aluminum binary hydrotalcite coating prepared in Comparative Example 1; Figure 3 XRD patterns of the zinc-magnesium-aluminum ternary hydrotalcite coating prepared in Example 3 and the magnesium-aluminum binary hydrotalcite coating prepared in Comparative Example 1; Figure 4 Electrochemical impedance spectra of the zinc-magnesium-aluminum ternary hydrotalcite coatings prepared in Examples 1-4 and the magnesium-aluminum binary hydrotalcite coatings prepared in Comparative Example 1, as well as the aluminum alloy substrate; Figure 5Electrochemical polarization curves of the zinc-magnesium-aluminum ternary hydrotalcite coatings prepared in Examples 1-4, the magnesium-aluminum binary hydrotalcite coatings prepared in Comparative Example 1, and the aluminum alloy substrate. DETAILED DESCRIPTION

[0017] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments. The following embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention.

[0018] Example 1 A method for in-situ growing a zinc-magnesium-aluminum ternary hydrotalcite coating on an aluminum alloy surface, comprising the following specific steps: 1. Cut the 5052 aluminum alloy substrate into a size of 20mm×15mm×1mm (length×width×height), polish the sample with water-resistant SiC sandpaper with a sandpaper size of 800#-2000#, wash it with distilled water, and then ultrasonically clean it with ethanol solution for 10 minutes, then ultrasonically clean it with deionized water for 10 minutes and dry it with cold air to obtain the pretreated aluminum alloy substrate; 2. Dissolve 0.1M magnesium nitrate, 0.005M zinc nitrate, and 0.1M urea in deionized water, adjust the pH to 10.0±0.2 with 1.0mol / L NaOH solution, and then place in a magnetic stirrer and stir for 30 minutes to obtain an in-situ growth solution; 3. Place the aluminum alloy substrate treated in step 1 flat on the bottom of the beaker, then pour the in-situ growth solution prepared in step 2 and seal the beaker with plastic wrap, and finally place it in a water bath for in-situ growth. The reaction temperature is 80±1°C and the reaction time is 12h; 4. After the reaction is completed, wash it with deionized water, blow it dry with cold air, and dry it in a drying oven at 60°C for 12 hours to obtain an aluminum alloy sample with a zinc-magnesium-aluminum ternary hydrotalcite coating. Figure 1 (a) is a scanning electron microscope photograph of the zinc-magnesium-aluminum ternary hydrotalcite coating on the aluminum alloy surface obtained in Example 1.

[0019] Example 2 A method for in-situ growing a zinc-magnesium-aluminum ternary hydrotalcite coating on an aluminum alloy surface, comprising the following specific steps: 1. Cut the 5052 aluminum alloy substrate into a size of 20mm×15mm×1mm (length×width×height), polish the sample with water-resistant SiC sandpaper with a sandpaper size of 800#-2000#, wash it with distilled water, and then ultrasonically clean it with ethanol solution for 15 minutes, then ultrasonically clean it with deionized water for 10 minutes and dry it with cold air to obtain the pretreated aluminum alloy substrate; 2. Dissolve 0.1M magnesium nitrate, 0.01M zinc nitrate, and 0.5M urea in deionized water, adjust the pH to 11.0±0.2 with 1.0mol / L NaOH solution, and then stir in a magnetic stirrer for 30 minutes to obtain an in-situ growth solution; 3. Place the aluminum alloy substrate treated in step 1 flat on the bottom of the beaker, then pour the in-situ growth solution prepared in step 2 and seal the beaker with plastic wrap, and finally place it in a water bath for in-situ growth. The reaction temperature is 75±1°C and the reaction time is 8h; 4. After the reaction is completed, wash it with deionized water, blow it dry with cold air, and dry it in a drying oven at 60°C for 12 hours to obtain an aluminum alloy sample with a zinc-magnesium-aluminum ternary hydrotalcite coating. Figure 1 (b) is a scanning electron microscope photograph of the zinc-magnesium-aluminum ternary hydrotalcite coating on the aluminum alloy surface obtained in Example 2.

[0020] Example 3 A method for in-situ growing a zinc-magnesium-aluminum ternary hydrotalcite coating on an aluminum alloy surface, comprising the following specific steps: 1. Cut the 5052 aluminum alloy substrate into a size of 20mm×15mm×1mm (length×width×height), polish the sample with water-resistant SiC sandpaper with a sandpaper size of 800#-2000#, wash it with distilled water, and then ultrasonically clean it with ethanol solution for 20 minutes, then ultrasonically clean it with deionized water for 10 minutes and dry it with cold air to obtain the pretreated aluminum alloy substrate; 2. Dissolve 0.1M magnesium nitrate, 0.02M zinc nitrate, and 0.5M urea in deionized water, adjust the pH to 8.0±0.2 with 1.0mol / L NaOH solution, and then place in a magnetic stirrer and stir for 30 minutes to obtain an in-situ growth solution; 3. Place the aluminum alloy substrate treated in step 1 flat on the bottom of the beaker, then pour the in-situ growth solution prepared in step 2 and seal the beaker with plastic wrap, and finally place it in a water bath for in-situ growth. The reaction temperature is 85±1°C and the reaction time is 18h; 4. After the reaction is completed, wash it with deionized water, blow it dry with cold air, and dry it in a drying oven at 60°C for 12 hours to obtain an aluminum alloy sample with a zinc-magnesium-aluminum ternary hydrotalcite coating. Figure 1 (c) is a scanning electron microscope photograph of the zinc-magnesium-aluminum ternary hydrotalcite coating on the aluminum alloy surface obtained in Example 3.

[0021] Example 4 A method for in-situ growing a zinc-magnesium-aluminum ternary hydrotalcite coating on an aluminum alloy surface, comprising the following specific steps: 1. Cut the 5052 aluminum alloy substrate into a size of 20mm×15mm×1mm (length×width×height), polish the sample with water-resistant SiC sandpaper with a sandpaper size of 800#-2000#, wash it with distilled water, and then ultrasonically clean it with ethanol solution for 15 minutes, then ultrasonically clean it with deionized water for 10 minutes and dry it with cold air to obtain the pretreated aluminum alloy substrate; 2. Dissolve 0.1M magnesium nitrate, 0.05M zinc nitrate, and 0.2M urea in deionized water, adjust the pH to 9.0±0.2 with 1.0mol / L NaOH solution, and then stir in a magnetic stirrer for 30 minutes to obtain an in-situ growth solution; 3. Place the aluminum alloy substrate treated in step 1 flat on the bottom of the beaker, then pour the in-situ growth solution prepared in step 2 and seal the beaker with plastic wrap, and finally place it in a water bath for in-situ growth. The reaction temperature is 65±1°C and the reaction time is 24h; 4. After the reaction is completed, wash it with deionized water, blow it dry with cold air, and dry it in a drying oven at 60°C for 12 hours to obtain an aluminum alloy sample with a zinc-magnesium-aluminum ternary hydrotalcite coating. Figure 1 (d) is a scanning electron microscope photograph of the zinc-magnesium-aluminum ternary hydrotalcite coating on the aluminum alloy surface obtained in Example 4.

[0022] Comparative Example 1 1. Cut the 5052 aluminum alloy substrate into 20mm×15mm×1mm (length×width×height) size, polish the sample with water-resistant SiC sandpaper with sandpaper size of 800#-2000#, wash with distilled water, and then ultrasonically clean with ethanol solution for 15 minutes, then ultrasonically clean with deionized water for 20 minutes and dry with cold air to obtain the pretreated aluminum alloy substrate; 2. Dissolve 0.1M magnesium nitrate and 0.5M urea in deionized water, adjust the pH to 8.0±0.2 with 1.0mol / L NaOH solution, and then stir in a magnetic stirrer for 30 minutes to obtain an in-situ growth solution; 3. Place the aluminum alloy substrate treated in step 1 flat on the bottom of the beaker, then pour the in-situ growth solution prepared in step 2 and seal the beaker with plastic wrap, and finally place it in a water bath for in-situ growth. The reaction temperature is 85±1°C and the reaction time is 18h; 4. After the reaction is completed, wash it with deionized water, blow it dry with cold air, and dry it in a drying oven at 60°C for 12 hours to obtain an aluminum alloy sample with a magnesium-aluminum binary hydrotalcite coating. Figure 1 (e) is a scanning electron microscope photograph of the magnesium-aluminum binary hydrotalcite coating on the aluminum alloy surface obtained in Comparative Example 1.

[0023] The difference between this comparative example and Example 3 is that in step 2, no 0.02 M zinc nitrate solution is added.

[0024] Characterization Test Example 1 The zinc-magnesium-aluminum ternary hydrotalcite coatings prepared in Examples 1-4 and the magnesium-aluminum binary hydrotalcite coating prepared in Comparative Example 1 were tested by scanning electron microscopy. The results are as follows: Figure 1 As shown; Depend on Figure 1 (a)-(d) It can be seen that the Zn-Mg-Al ternary hydrotalcite coating has a typical hydrotalcite flaky structure. The surface of the film is uniform, flat, dense and has no agglomeration phenomenon. After the addition of zinc, the flaky structure of the hydrotalcite will bend. Figure 1 (e) is a magnesium-aluminum binary hydrotalcite coating prepared without adding zinc. It can be seen from the figure that the magnesium-aluminum binary hydrotalcite coating forms a flaky structure, shows a tendency to agglomerate, and is relatively thin. Scratches on the substrate are vaguely visible in some parts.

[0025] Characterization Test Example 2 The EDS spectra of the zinc-magnesium-aluminum ternary hydrotalcite coating prepared in Example 3 and the magnesium-aluminum binary hydrotalcite coating prepared in Comparative Example 1 are as follows: Figure 2 As shown; Depend on Figure 2 (a) It can be seen that the Zn-Mg-Al ternary hydrotalcite coating contains five elements: N, O, Mg, Al, and Zn. The Al element is provided by the aluminum alloy substrate, and Mg, Zn, and N all come from the in-situ growth solution. The presence of Mg and Zn elements indicates that the Zn-Mg-Al ternary hydrotalcite coating has been successfully prepared on the surface of the aluminum alloy substrate. Figure 2 (b) is the EDS spectrum of the magnesium-aluminum binary hydrotalcite coating prepared without adding zinc. It can be seen from the figure that the magnesium-aluminum binary hydrotalcite coating has four elements: N, O, Mg, and Al. The Al element is also provided by the aluminum alloy matrix. The presence of the Mg element indicates that the magnesium-aluminum binary hydrotalcite coating has been successfully prepared.

[0026] Characterization Test Example 3 The XRD spectra of the zinc-magnesium-aluminum ternary hydrotalcite coating prepared in Example 3 and the magnesium-aluminum binary hydrotalcite coating prepared in Comparative Example 1 are shown in FIG. Figure 3 As shown; Depend on Figure 3 It can be seen that the zinc-magnesium-aluminum ternary hydrotalcite coating prepared in Example 3 exhibits typical (003) and (006) crystal plane characteristic diffraction peaks of hydrotalcite at 12° and 24°, respectively, and the diffraction peaks are sharp, indicating good crystallinity; the diffraction peaks of the magnesium-aluminum binary hydrotalcite coating prepared in Comparative Example 1 are not obvious, which may be due to the fact that the prepared coating is relatively thin, so the diffraction peak intensity is low and not obvious.

[0027] Characterization Test Example 4 The electrochemical properties of the zinc-magnesium-aluminum ternary hydrotalcite coatings prepared in Examples 1-4 and the magnesium-aluminum binary hydrotalcite coatings prepared in Comparative Example 1 and the aluminum alloy substrate were characterized. Figure 4 and Figure 5 As shown; Only 1cm×1cm area was retained for the tested coatings, and the rest was completely coated with peelable red glue. At room temperature, the zinc-magnesium-aluminum ternary hydrotalcite coating, the magnesium-aluminum binary hydrotalcite coating and the aluminum alloy substrate were used as working electrodes, saturated calomel was used as the reference electrode, graphite was used as the counter electrode, and the corrosion medium was 3.5% NaCl solution; Depend on Figure 4 and Figure 5 It can be seen that the corrosion resistance of the zinc-magnesium-aluminum ternary hydrotalcite coatings prepared in Examples 1-4 and the magnesium-aluminum binary hydrotalcite coatings prepared in Comparative Example 1 are much higher than that of the aluminum alloy substrate, and the corrosion resistance of the zinc-magnesium-aluminum ternary hydrotalcite coating is higher than that of the magnesium-aluminum binary hydrotalcite coating.

[0028] The electrochemical properties of the zinc-magnesium-aluminum hydrotalcite coatings prepared in Examples 1-4, the magnesium-aluminum binary hydrotalcite coatings prepared in Comparative Example 1, and the aluminum alloy substrate were characterized. The fitting results of the electrochemical property characterization data involved are shown in Table 1.

[0029] Table 1

[0030] It can be seen from Table 1 that the corrosion resistance of the zinc-magnesium-aluminum ternary hydrotalcite coatings prepared in Examples 1-4 of the present invention and the magnesium-aluminum binary hydrotalcite coating prepared in Comparative Example 1 is significantly better than that of the aluminum alloy substrate. Example 4 has a higher charge transfer resistance of 1.16×10 7 Ω·cm 2 , which is 4 orders of magnitude higher than that of the aluminum alloy substrate and 1 order of magnitude higher than that of the comparative example 1; at the same time, Example 4 has a higher self-corrosion potential of -0.705 V and a smaller self-corrosion current density of 5.58×10 -9 A.cm -2 , indicating that the zinc-magnesium-aluminum ternary hydrotalcite coating prepared in Example 4 of the present invention has better corrosion resistance.

[0031] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for in-situ growth of a zinc-magnesium-aluminum ternary hydrotalcite coating on an aluminum alloy surface, characterized in that: The specific steps of the method are: a. Pre-treat the aluminum alloy surface; b. Prepare in situ growth solution: dissolve 0.005-0.1M magnesium nitrate, 0.005-0.1M zinc nitrate and 0.1-0.5M urea in deionized water, adjust the pH to 8-11, and then stir in a magnetic stirrer to prepare an in situ growth solution; c. In-situ growth of hydrotalcite coating: the pre-treated aluminum alloy is placed in an in-situ growth solution for in-situ growth, the reaction temperature is 65 to 95°C, and the reaction time is 6 to 24 hours; d. Cleaning and drying: Rinse the aluminum alloy after the reaction with deionized water and then dry it in a drying oven at 60°C for 12 hours.

2. The method according to claim 1, characterized in that The grade of the aluminum alloy in step a is 5052.

3. The method according to claim 1, characterized in that The aluminum alloy surface pretreatment in step a comprises the following steps: polishing with 800#-2000# sandpaper to remove oxides and pollutants on the surface of the aluminum alloy, polishing and rinsing, and then immersing in ethanol solution and deionized water for ultrasonic cleaning, and drying.

4. The method according to claim 1, characterized in that: In step b, 1 mol / L NaOH solution is used to adjust the pH.

5. The method according to claim 1, characterized in that The magnetic stirring time in step b is 30 minutes.

6. A zinc-magnesium-aluminum hydrotalcite coating on the surface of an aluminum alloy obtained according to the method described in any one of claims 1 to 5.

Citation Information

Patent Citations

  • Aluminum and aluminum alloy surface self-repairing and corrosion-resisting conversion coating and preparation method thereof

    CN103184447B

  • Preparation method for anti-corrosion Mg-Al LDH / MAO composite coating of aluminum alloy

    CN109853022A